Havelock Ellis correspondence and photograph - Ellis, Havelock, 1859-1939.
TLS (1933 October 18; London, England) from Ellis to an unidentified individual concerning the confusion between sex and sin in the western world and the availability of Ellis's book titled, Die Erotik in der Kunst (circa 1913). Includes an undated photograph of Ellis.
British psychologist and author. Full name: Henry Havelock Ellis.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Psychology; Sex; Sin; Authors; Psychologists